CMIP6 global wind-wave 21st century climate projections phase 2 ... - Meucci, Alberto; Young, Ian; Trenham, Claire; Hemer, Mark (CSIRO, 2023)
This dataset contains archived 3-hourly outputs from wave climate simulations at 0.5-degree global grid resolution carried out using an Irregular-Regular-Irregular (IRI) three-grid system to model the polar regions, and implemented in WaveWatch III (v6.07). The model configuration is outlined in manuscripts: - Meucci A., Young I. R., Hemer M., Trenham C., and Watterson I. 2023. 140 Years of Global Ocean Wind-wave Climate Derived from CMIP6 ACCESS-CM2 and EC-Earth3 GCMs. Global Trends, Regional Changes, and Future Projections. Journal of Climate, 1-56. DOI: https://doi.org/10.1175/JCLI-D-21-0929.1 - Meucci A., Young I.R., Trenham C. and Hemer M., (in prep). CMIP6-derived wave climate observation-based model ensemble. Wave model forcing consisted of surface wind and sea-ice concentration fields from 6 CMIP6 models. The model is run with the latest observation-based source term parametrization ST6, using wind-drag coefficient "CDFAC" parameter value of 1. Archived variables, in monthly netCDF files for all ...